Femoral metastasis in previously treated bladder cancer patient: A case report - Tala Jouma Alhejazi; Hassan Bdeiwi; Mohamad W. Sukkari; Mohamad Ibrahim; Ammar Sukari; Hani Alloush (Clinical Case Reports, 2022)
Abstract Although treated appropriately, bladder cancer can recur and metastasize. We are reporting the case of a patient with a well‐cured bladder cancer who presented after 14 months with femoral pain which turned out to be a bony metastasis. The patient underwent surgical excision followed by chemotherapy.